2023
DOI: 10.3389/fmars.2023.992179
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling cultivation of Saccharina latissima on net or line systems; comparing biomass yields and nutrient extraction potentials

Abstract: Production of sugar kelp, Saccharina latissima, has the potential of extracting nutrients and carbon from the seawater and returning it to land as a bioresource. The production thereby acts as an emission capture and utilization instrument contributing to mitigation of eutrophication and climate change. To achieve higher biomass yields improving the effects on climate and environment, and the economic feasibility of the production, cultivation techniques need to be optimized. In Denmark so far, S. latissima pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…After a successful nursery stage, the timing of outplanting (season) is the crucial next step for efficient kelp aquaculture (Peteiro and Freire 2012;Hurd et al 2014a;Peteiro et al 2016;Boderskov et al 2023). This study found a seasonal influence on the development of L. corrugata at sea.…”
Section: At-sea Cultivation: Seasons and Depthsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a successful nursery stage, the timing of outplanting (season) is the crucial next step for efficient kelp aquaculture (Peteiro and Freire 2012;Hurd et al 2014a;Peteiro et al 2016;Boderskov et al 2023). This study found a seasonal influence on the development of L. corrugata at sea.…”
Section: At-sea Cultivation: Seasons and Depthsmentioning
confidence: 99%
“…Understanding the best season (time) for out-planting is also critical for optimising seaweed production but can be challenging since most abiotic and biotic variables that can impact cultivation outcomes vary spatially and temporally (Hurd et al 2014b;Roleda and Hurd 2019;Boderskov et al 2023). Depending on the location, nutrient concentrations, light penetration, seawater temperature, and water motion can vary dramatically between seasons and depths (Brown et al 1997;Ganesan et al 2006;Handå et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The model assumes that if salinity is optimal, the optimal biomass potential can be reached 99 . Therefore, the model output might overestimate the production potential in areas where nutrients, temperature, light, or a combination of these are limiting growth 100 .…”
Section: Methodsmentioning
confidence: 99%
“…They assess that pathogens known from the Asian species Saccharina japonica could be of risk for its close relative, S. latissima, which is widely cultivated in the Nordic countries, including Denmark, the Faroe Islands, Greenland, Norway, and Sweden (Broch et al, 2019;Visch et al, 2020;Wegeberg, Geertz-Hansen and Mols-Mortensen, 2021;Boderskov, Rasmussen and Bruhn, 2023;ICES, 2023).…”
Section: Pathogens Transfer and Dispersalmentioning
confidence: 99%